Comparison of the effectiveness and safety of perampanel and oxcarbazepine as monotherapy in children and adolescents with newly diagnosed focal epilepsy - Yi, Jia-Qin; Huang, Sheng; Wu, Miao-Juan; Ma, Jie-Hui; Huang, Li-Juan; Liang, Song; Sun, Dan (Frontiers in Pharmacology, 2023)
Objective: This study aims to compare the effectiveness and safety of perampanel and oxcarbazepine as monotherapy in children with focal epilepsy (FE). Methods: This is an ambispective, single-center, non-inferiority study comparing the effectiveness and safety of perampanel (PER) monotherapy and oxcarbazepine (OXC) monotherapy in children with newly diagnosed FE. The primary endpoint was a six-month seizure freedom rate. The secondary endpoints included retention, responder, and seizure freedom rates at 3, 6, and 12 months, respectively. Adverse events (AEs) were also recorded for both groups. Results: One hundred and thirty children and adolescents aged from 4 to 18years newly diagnosed with FE between May 2020 and November 2022 in Wuhan Children’s Hospital were included. There were 71 patients in the PER group and 59 patients in the OXC group. In the per protocol set (PPS), 50 (78.1%) in the PER group and 43 (78.2%) in the OXC group completed six months of treatment without seizures. The lower 95% CI (66.0%–87.5%) limit of PER was higher than the non-inferiority margin of 62.4% (80% of the 6-month seizure freedom rate in the OXC group); PER was non-inferior to OXC. The 3-month and 12-month seizure freedom rates were 77.1% and 82.9% for the PER group, respectively, while they were 80.4% and 75.8% for the OXC group. There were no serious adverse events in both groups. Conclusion: PER showed comparable effectiveness and safety compared with OXC in children with newly diagnosed focal epilepsy, which might be an effective and safe treatment for children and adolescents with newly diagnosed FE. Clinical Trial Registration: Identifier ChiCTR2300074696